A new protein (J1-31 antigen, 30 kD) is expressed by astrocytes, Müller glia and ependyma. Issue 6 (June 1987) - Predy, R.; Singh, D.; Bhatnagar, R.; Singh, R.; Malhotra, S. K.
Abstract : Monoclonal antibody (MAb) J1–31 raised using human brain homogenate as immunogen in mice can be used as a cell type marker for certain types of CNS macroglia, namely astrocytes, Müller cells and tanycytes as well as ciliated ependymal cells. Except for the ciliated ependymal cells, these types of macroglia express glial fibrillary acidic protein (GFAP). J1–31 antigen is an intracellular protein which has a MW of 30 kD under reducing conditions for gel electrophoresis (Singh et al., 1986). This protein is distinct from GFAP (MW 50 kD) and vimentin (MW 55 kD), the two core proteins of 10 nm IFs known to be expressed in the above types ofmacroglia. This conclusion is based on several criteria including temporal differences in the onset of expression of GFAP and J1–31 antigen during development of the rat cerebellum. Also, there is no detectable (by immunofluorescence microscopy) expression of J1–31 antigen in the prenatal CNS or outside the CNS where vimentin has been reported to be abundant. The most direct evidence that J 1–31 antigen and GFAP are distinct proteins comes from studies on the mature ciliated ependymal cells which do not express GFAP and yet show intense immunostaining for J1–31 antigen.